Kinetic Study of Enzymatic Oxidation On Glycerol with Immobilised Laccase/TEMPO System - Chi, Shein Hong; Chin, S. Y.; Chin, Fui Cheng; Mohd Sabri, Mahmud; Chua, Gek Kee (2015)
Glycerol, a byproduct of biodiesel has a great potential in producing valuable fine chemicals. Current catalytic oxidation methods based on noble metal have their drawbacks on environment. Towards this end, an enzymatic oxidation of glycerol by laccase from Trametes Versicolor and TEMPO (2,2,6,6-tetramethylpiperidine-N-oxyl)to produce glyceric acid seems to be a promising approach. Immobilisation of enzyme increased laccase stability and reusability. Glycerol as initial reactant for the oxidation process selectively oxygenates by immobilised laccase/TEMPO leads to a complex system with different reaction rate for each component. Glycerol was incubated with 30mM of TEMPO with the presence of immobilised laccase for 24hours. Products were quantified by using HPLC.A kinetic model of the glycerol oxidation was developed. The whole reaction was divided into 2 steps. Experimental data calculated results for each step were obtained with good agreement. From the data, the kinetic for all the components was identified as well. These results can be used in developing new greener catalyst with high activity, selectivity and stability for glyceric acid.